Pengembangan Bahan Ajar Digital Berbasis PBL untuk Meningkatkan Hasil Belajar Ekonomi Siswa - Hamzah Isfahani; Saidun Hutasuhut; Zulkarnain Siregar (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The objective of this research is to create digital teaching materials utilizing Problem-Based Learning (PBL) methodology. The goal is to help kids in class XI IPS 1 at MAN 2 Langkat learn more about economics. Based on what Borg and Gall said about research and development (R&D), this study is being done. The research and development implementation in this study utilized a total of seven procedures or stages. This simplification was necessitated by various factors, such as time and cost constraints. Additionally, Borg and Gall's perspective on limiting research and development to a smaller scale, including the number of research steps in a thesis or dissertation, also influenced this decision. The present study was conducted at MAN 2 Langkat, involving a sample of 34 students from class XI IPS 1. Based on the feasibility validation test conducted by experts on PBL-based digital teaching materials, the average score obtained was 85.73, indicating a high level of feasibility. The average posttest score for the experimental class which was treated with PBL-based digital teaching materials that was developed was 89,82, while the posttest score for the control class which was given teaching materials from the school averaged 86,29. These results indicate that PBL-based digital teaching materials are effective in use. Furthermore, the results of the 2-way ANOVA test stated that the 2-tailed Sig. was 0.229 < 0.05. Therefore, it can be concluded that there is no significant interaction in student economic learning outcomes between students with high and low literacy skills who are taught using PBL-based digital teaching materials and those who are not.